Analysis of Fertile Age Couples Interest Using IUD as a Contraception Method Based on Factors Affecting in Sugihwaras Public Health Center - Puji lestari; Byba Melda Suhita; Katmini Katmini (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
CCA interest in using an IUD as an IUD (Contraception Tool in the Womb) in the work area of ​​the Sugihwaras Community Health Center is still low. This is caused by several factors. The purpose of this research is to find out the most dominant factor influencing CCA interest in using an IUD as a contraceptive device in the work area of ​​the Puskesmas Sugihwaras Bojonegoro. The design of this study used an observational method with a cross sectional approach. With a population of all couples of childbearing age who use the IUD as a contraceptive in the work area of ​​the Sugihwaras Health Center, which is 175 people. By using purposive sampling technique obtained a sample size of 122 respondents. The independent variables in this study were acceptor confidence, service quality, environmental culture, and family support. While the dependent variable is CCA interest in using an IUD as a contraceptive. The results showed that the p value for the acceptor confidence variable was 0.017 <0.05 so that the acceptor confidence variable had an influence on the acceptor's interest. P value of service quality 0,000 <0.05 so that service quality variables have an influence on the acceptor's interest. P value of environmental culture 0.035 <0.05 so that environmental culture has an influence on the acceptor's interest. P value of family support 0.001 <0.05 so that family support has an influence on the acceptor's interest. Of all the independent variables that have the strongest signification value is service quality. So the hypothesis is accepted. That means that service quality is the factor that has the most influence on CCA interest in using an IUD as a contraceptive in the work area of ​​the Sugihwaras Community Health Center.